2017
DOI: 10.1002/oby.21873
|View full text |Cite
|
Sign up to set email alerts
|

Association between consistent weight gain tracking and gestational weight gain: Secondary analysis of a randomized trial

Abstract: Objective-The effective components of interventions for reducing excessive gestational weight gain (GWG) remain to be identified. This study investigated the socio-demographic, physical, psychosocial, and environmental correlates of online GWG tracking and its independent association GWG outcomes.Methods-898 women in the intervention arms of a randomized trial assessing the effectiveness of an integrated online and mobile phone behavioral intervention to decrease the prevalence of excessive GWG were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…In the postpartum phase given the well-documented value of self-monitoring in weight management studies. 41,42 Positive overall feedback on self-monitoring, including perceived helpfulness and ease of using the tracking app may have contributed to these high tracking rates. The finding that 73% (n = 8) of participants tracked their exercise less than 30% of the recommended days, 45% (n = 5) of whom tracked 10% of these days or less, may be a reflection of the barriers that pregnant women face (e.g., physical discomfort, fatigue, soreness; body image issues; concern about injury).…”
Section: Discussionmentioning
confidence: 99%
“…In the postpartum phase given the well-documented value of self-monitoring in weight management studies. 41,42 Positive overall feedback on self-monitoring, including perceived helpfulness and ease of using the tracking app may have contributed to these high tracking rates. The finding that 73% (n = 8) of participants tracked their exercise less than 30% of the recommended days, 45% (n = 5) of whom tracked 10% of these days or less, may be a reflection of the barriers that pregnant women face (e.g., physical discomfort, fatigue, soreness; body image issues; concern about injury).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 135 of the 1126 women in the intervention group (12%) only viewed placebo control content, essentially self-assigning themselves to the control group. The weight gain tracker was the most widely used behavior change tool with 70% of intervention arm women using the tool at least once [ 14 ] and 27.3% using it consistently across pregnancy [ 27 ]. In an analysis of usage of intervention website features, using the weight gain tracker consistently across pregnancy was associated with a reduction in the proportion of women with excessive total and weekly GWG and mean total GWG among not-low income women [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Lindberg and Anderson developed a best practice alert based on prepregnancy BMI that included an individualized total weight gain recommendation, weekly weight gain goals, a script for prenatal care provider counseling, a template for documentation, and a patient handout, improving the consistency and accuracy of counseling . A recent study tested the effectiveness of an online and mobile phone application providing personalized GWG tracking information, as well as a diet and physical activity goal setting tool . Results indicated that Medicaid‐eligible participants were significantly less likely to consistently participate.…”
Section: Preventative Measuresmentioning
confidence: 99%
“…Results indicated that Medicaid‐eligible participants were significantly less likely to consistently participate. Among women without low incomes, consistent use of the program was associated with a reduced risk of excessive GWG (RR, 0.73; 95% CI, 0.59‐0.89; P = .002) and with 2.35 kg less GWG on average (95% CI, −3.23 to −1.46; P < .0001) . Appropriate use of technology may offer women and prenatal care providers additional tools to help meet GWG recommendations for women who are able to use these resources.…”
Section: Preventative Measuresmentioning
confidence: 99%